Conceptual Space of Image in the Psychological Literature - Bilyk, T. M. (Psychological Prospects Journal, 2011)
The results of theoretical analysis of concept image are highlighted in the article. Theoretical conclusion of main conceptual lines of image definition and structure is proposed.
Keywords: image; an image; reputation; authority; a stere